ANALISIS GAYA KEPEMIMPINAN, HUBUNGAN ANTAR KARYAWAN, DAN KONDISI KERJA TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI DENGAN METODE STUCTURAL EQUATION MODELING ( SEM ) AMOS DI PT. XYZ - Ali Akbar; Osep Hijuzaman; Irvan Mohammad Regent; Wanwan Jamaludin (Jurnal Teknologika, 2023)
PT. XYZ is a manufacturing company that produces Silent Chain and Rim, during the period September 2022 – February 2023 according to data from the Production Department the level of NG goods in the period increased compared to the previous period. Many factors affect the level of NG goods, one of which is the Performance of PT. XYZ. This study aims to determine the influence of leadership style, relationships between employees, and working conditions on the performance of PT. XYZ. The sampling method used was simple random sampling and determining the number of samples in this study using the slovin formula resulted in 161 respondents, the data used were primary data with questionnaire techniques, hypothesis testing was carried out with multiple linear regression analysis techniques using two-tailed tests with the Analysis of moment structure version 24 application . The results showed that there was no influence between the variables of Relationship Between Employees on Employee Performance with a value of P>0.05 while Leadership Style and Working Conditions had an effect on Employee Performance with a value of P<0.05